Protecting Your Pet from Pesticides - Frederick M. Fishel (EDIS)
PI-81, a 3-page fact sheet by Frederick M. Fishel, explains precautionary measures that can be used to protect pets from injury due to pesticides used in and around the home. Includes additional sources of information. Published by the UF Department of Agronomy, May 2010.